Regional Angiogenesis With Vascular Endothelial Growth Factor in Peripheral Arterial Disease: A Phase II Randomized, Double-Blind, Controlled Study of Adenoviral Delivery of Vascular Endothelial Growth Factor 121 in Patients With Disabling Intermittent Claudication - Rajagopalan, Sanjay; Mohler, Emile R.; Lederman, Robert J.; Mendelsohn, Farrell O.; Saucedo, Jorge F.; Goldman, Corey K.; Blebea, John; Macko, Jennifer; Kessler, Paul D.; Rasmussen, Henrik S.; Annex, Brian H. (Circulation (New York, N.Y.), 2003)
Background— “Therapeutic angiogenesis” seeks to improve perfusion by the growth of new blood vessels. The Regional Angiogenesis with Vascular Endothelial growth factor (RAVE) trial is the first major randomized study of adenoviral vascular endothelial growth factor (VEGF) gene transfer for the treatment of peripheral artery disease (PAD). Methods and Results— This phase 2, double-blind, placebo-controlled study was designed to test the efficacy and safety of intramuscular delivery of AdVEGF121, a replication-deficient adenovirus encoding the 121-amino-acid isoform of vascular endothelial growth factor, to the lower extremities of subjects with unilateral PAD. In all, 105 subjects with unilateral exercise-limiting intermittent claudication during 2 qualifying treadmill tests, with peak walking time (PWT) between 1 to 10 minutes, were stratified on the basis of diabetic status and randomized to low-dose (4×10 9 PU) AdVEGF121, high-dose (4×10 10 PU) AdVEGF121, or placebo, administered as 20 intramuscular injections to the index leg in a single session. The primary efficacy end point, change in PWT (ΔPWT) at 12 weeks, did not differ between the placebo (1.8±3.2 minutes), low-dose (1.6±1.9 minutes), and high-dose (1.5±3.1 minutes) groups. Secondary measures, including ΔPWT, ankle-brachial index, claudication onset time, and quality-of-life measures (SF-36 and Walking Impairment Questionnaire), were also similar among groups at 12 and 26 weeks. AdVEGF121 administration was associated with increased peripheral edema. Conclusions— A single unilateral intramuscular administration of AdVEGF121 was not associated with improved exercise performance or quality of life in this study. This study does not support local delivery of single-dose VEGF 121 as a treatment strategy in patients with unilateral PAD.